A smart software radio concept development and demonstration. - Patti, J.J.
A testbed system was developed for smart networking radio algorithms. The associated modular software environment and Phase I hardware testbed are described. It provides the framework for the development of advanced processing algorithms, adaptive multirate systems, and operational radio algorithms and modules. Modular software radio technology allows for the insertion of new algorithms, the quantitative characterization of waveform performance, and the separation of the waveform definition from the details of the implementation to enhance portability. The testbed is representative of SPEAKeasy II-class open architecture software radios. The FLIPWAVE spread-spectrum modem invented at the US Air Force Research Laboratory (AFRL) was developed and evaluated using this testbed. The waveform is presented with experimental results. A unique feature of this modem is a new single-channel quadraphase differential RAKE receiver processor, which illustrates the contributions of the testbed toward the flexibility and portability of novel modems
Keywords: AFRL; FLIPWAVE spread-spectrum modem; SPEAKeasy II-class open architecture software radios; US Air Force Research Laboratory; Adaptive multirate systems; Advanced processing algorithms; Demonstration; Experimental results; Hardware testbed; Modular software environment; Modular software radio technology; Operational radio algorithms; Operational radio modules; Portability; Quadraphase differential RAKE receiver processor; Single-channel receiver processor; Smart networking radio algorithms; Smart software radio; Testbed system; Waveform performance